Enhancing Speaking Skills in the Material of Remedial Learning Through Community Language Learning in SMP Multazam Semarang - Muhamad Zayyinul Muttaqin (Universitas Islam Negeri Walisongo Semarang, 2019)
This paper highlighted how extremely English language learning that sometimes seemed threatening pupils in the classroom where they were unable to express much attention and confidence. They quantitatively got the worst score for this subject due to several aspects that must be comprehended by students: pronunciation, grammatical structure, vocabulary, and intonation. As long as, students participated in the teaching-learning process, they had standardly done all of the assessment. Therefore, teachers here as the facilitator or counselor should redesign the classroom’s atmosphere and its method; instead, it would invite students to show their best performance. Community Language Learning (CLL) displayed how effectively and efficiently English should be taught. Thus, this research is qualitatively reported to observe how CLL was able to increase the students’ speaking skill in the Material of Remedial Learning for students’ eight grade in SMP Multazam with the total number of 26 students. An observation sheet and the score ranking sheet were as data collection to consider the names. A fluency, a pronunciation, an expression, a vocabulary, and content were the instrument to analysis their performance. This study was Classroom Action Research which revealed that the students are comfortable in joining learning’s experience, and its effects to their competence in speaking skill with the amount of enhancement through 2 cycles; post-test 1 and post-test 2. CLL was considered to be an effective method since it contributed to the prominent effect of speaking skill.